2012
DOI: 10.1186/bcr3115
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of CXCR3 ligand secretion by prostaglandin E2 and cyclooxygenase inhibitors in human breast cancer

Abstract: IntroductionIn murine breast cancer models, the two interferon-gamma (IFN-γ) inducible chemokines and CXC-chemokine receptor 3 (CXCR3) receptor ligands, monokine induced by γ-interferon (CXCL9) and interferon-γ-inducible protein-10 (CXCL10) impair tumor growth and metastasis formation through recruitment of natural killer (NK) cells and tumor-suppressive T lymphocytes. In human breast cancer, CXCL9 mRNA overexpression correlates with the number of tumor infiltrating lymphocytes and predicts response to differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 56 publications
3
63
0
1
Order By: Relevance
“…In addition, previous evidence has shown that inhibition of cyclooxygenases reduces tumor growth and incidence of metastases in a lymphocytic and IFN-γ-dependent manner. Thus, in a recently published study, Bronger et al (2012) hypothesized that the COX isoenzymes could be a pharmacologic target for the increase of intratumoral CXCR3 ligand concentration in human breast cancer. In that study, MCF-7 or MDA-MB-231 cells were treated with IFN-γ with or without PGE 2 or the COX inhibitors indomethacin, acetylsalicylic acid, and celecoxib.…”
Section: Effect On Immunosurveillancementioning
confidence: 98%
“…In addition, previous evidence has shown that inhibition of cyclooxygenases reduces tumor growth and incidence of metastases in a lymphocytic and IFN-γ-dependent manner. Thus, in a recently published study, Bronger et al (2012) hypothesized that the COX isoenzymes could be a pharmacologic target for the increase of intratumoral CXCR3 ligand concentration in human breast cancer. In that study, MCF-7 or MDA-MB-231 cells were treated with IFN-γ with or without PGE 2 or the COX inhibitors indomethacin, acetylsalicylic acid, and celecoxib.…”
Section: Effect On Immunosurveillancementioning
confidence: 98%
“…We found that high transcription levels of CXCL9 conferred an overall survival advantage in all BC patients, consistent with previous findings. Some researchers have already discovered that IFN-γ exhibits a powerful influence on the secretion and expression of CXCL9 and CXCL10 [41, 42]. The GeparSixto trial revealed that as an immune-activating factor, CXCL9 shows a positive correlation with PD-1 [43].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of CXCR3/ligand axis in cancer is further strengthened by the observations that COX-inhibitors increased CXCL9/CXCL10 expression [56] and promoted anti-tumor effects in breast cancer [57]. Bronger et al [56] demonstrated that suppressing endogenous PGE2 synthesis by cyclooxygenase inhibition increased CXCL9 and CXCL10 release from breast cancer cells and enhanced intra-tumoral immune infiltration.…”
Section: Therapeutic Implications Of Cxcr3/ligand Axis In Cancermentioning
confidence: 86%
“…Bronger et al [56] demonstrated that suppressing endogenous PGE2 synthesis by cyclooxygenase inhibition increased CXCL9 and CXCL10 release from breast cancer cells and enhanced intra-tumoral immune infiltration. In this study, the unselective COX inhibitors aspirin and indomethacin were preferable in increasing CXCL9/CXCL10 in comparison to celecoxib that at higher concentrations reduced ligand release from breast cancer cells.…”
Section: Therapeutic Implications Of Cxcr3/ligand Axis In Cancermentioning
confidence: 99%
See 1 more Smart Citation